2019
DOI: 10.1093/gbe/evz091
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Relatedness and Classification of Tumor-Inducing and Opine-Catabolic Plasmids in Three Rhizobium rhizogenes Strains Isolated from the Same Crown Gall Tumor

Abstract: Plasmids play a crucial role in the ecology of agrobacteria. In this study, we sequenced tumor-inducing (Ti) and opine-catabolic (OC) plasmids in three Rhizobium rhizogenes ( Agrobacterium biovar 2) strains isolated from the same crown gall tumor on “Colt” cherry rootstock and conducted comparative genomic analyses. Tumorigenic strains C5.7 and C6.5 carry nopaline-type Ti plasmids pTiC5.7/pTiC6.5, whereas the nonpathogenic strain Colt5.8 carries the nopaline-type O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…By a putative recombination event R4 part of the tra region of pTiC58 is deviant from that of the other nopaline Ti-plasmids. During the preparation of our manuscript, the characterization of the closely related nopaline Ti-plasmids pTiC5.7/pTiC6.5, which are almost identical to plasmid pTiKerr108 from our study, was reported and the relatedness of nopaline Ti-plasmids to nopaline catabolic plasmids was determined leading to the hypothesis that the nopaline Ti-plasmids are derived from such catabolic plasmids (Kuzmanović and Puławska 2019). Interestingly, the tra genes of the pTiC58 are more similar to those of nopaline catabolic plasmid pAtK84b (88% nucleotide identity) than to those of any of the other nopaline Ti-plasmids in our study, which would be in line with pTiC58 being the most ancestral of the studied plasmids and recombination event R4 occurring after formation of the ancestral nopaline Ti-plasmid, but before the transposition events leading to subgroups A and B.…”
Section: Discussionmentioning
confidence: 90%
“…By a putative recombination event R4 part of the tra region of pTiC58 is deviant from that of the other nopaline Ti-plasmids. During the preparation of our manuscript, the characterization of the closely related nopaline Ti-plasmids pTiC5.7/pTiC6.5, which are almost identical to plasmid pTiKerr108 from our study, was reported and the relatedness of nopaline Ti-plasmids to nopaline catabolic plasmids was determined leading to the hypothesis that the nopaline Ti-plasmids are derived from such catabolic plasmids (Kuzmanović and Puławska 2019). Interestingly, the tra genes of the pTiC58 are more similar to those of nopaline catabolic plasmid pAtK84b (88% nucleotide identity) than to those of any of the other nopaline Ti-plasmids in our study, which would be in line with pTiC58 being the most ancestral of the studied plasmids and recombination event R4 occurring after formation of the ancestral nopaline Ti-plasmid, but before the transposition events leading to subgroups A and B.…”
Section: Discussionmentioning
confidence: 90%
“…Except for the IEs, T-DNAa of plasmids pTi932 and pTi1078 was organized similarly to that of the right side of the T-DNA of the nopaline-type Ti plasmid pTiC5.7 (genes acs to nos ) ( fig. 4 a ), characterized in our previous study ( Kuzmanović and Puławska 2019 ). It was also evident that the right end of T-DNAa of the “tumorigenes” Ti plasmids (genes 6b - 3′ - nos ) had a higher degree of sequence identity with the corresponding T-DNA region of pTiC5.7 compared with the rest of the T-DNAa sequence ( fig.…”
Section: Resultsmentioning
confidence: 91%
“… Nabi et al (2022) investigated the diversity among T-DNAs and vir regions of 56 Ti/Ri plasmid sequences. In recent studies, complete sequences of several Ti/Ri plasmids and their relationship with related plasmids were investigated ( Hooykaas and Hooykaas 2021a , 2021 b ; Shao et al 2018 ; Kuzmanović and Puławska 2019 ; Shao et al 2019 ). Furthermore, Weisberg et al (2020) analyzed complete sequences of 143 Ti/Ri plasmids and classified them into nine distinct lineages (types) based on their evolutionary relationships, including six Ti (I–VI) and three Ri (I–III) types.…”
Section: Introductionmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 21, 2020. ; https://doi.org/10.1101/2020.12.19.423612 doi: bioRxiv preprint Surprisingly, we identified putative genes associated with catabolism of the opine agrocinopine harbored on a large circular chromosome of the reference strain S4. Thus far, such genes were reported as a plasmid-borne (Clare et al, 1990, Wetzel et al, 2014, Suzuki et al, 2000, Shao et al, 2018, Zhu et al, 2000, Kuzmanovid & Puławska, 2019, Shao et al, 2019. Therefore, their presence on a chromosome might be a result of the horizontal gene transfer.…”
Section: Specific Functions and Ecologies Suggested By Clade-specificmentioning
confidence: 99%